Enhancing industry engagement with work-integrated learning: Capacity building for industry partners - Ferns, Sonia; Russell, L.; Kay, J. (Asia-Pacific Journal of Cooperative Education, 2016)
Work-integrated learning (WIL) enables the embedding of relevant real-world learning into curriculum resulting in students that are better prepared to enter the workforce and meet demands of employers seeking work-ready graduates. Research confirms students who undertake WIL as part of their degree consistently achieve better employment outcomes. Industry's role in WIL is critical and, therefore, engagement with industry partners is essential to determine what is required to support their engagement and contribution to WIL. This Office of Learning and Teaching funded research project, aimed to determine the topics, format and mode of resources industry perceives as most useful The project used a mixed methods approach to gather data from a range of sources with findings confirming industry are seeking resources on assessment, feedback and supervision of students as well as information on clarification of roles and negotiating partnerships. The project outcomes informed the development of user-friendly and accessible resources for industry.